Verità e diritto; scienza, pseudoscienza e fake news - Simonetti, Luca (Chimica nella Scuola, 2024)
In Italy, academic freedom is guaranteed by the Constitution (article 33), but it has its limits, like all other liberties. First, it has to be reconciled with the right of the schools to decide what has to be taught and how, and with the students’ right to receive the best possible instruction as well. Secondly, academic freedom faces the normal limits of all expressions of thought, and it can therefore be limited if it endangers other rights or values also guaranteed by the Constitution (as it happened during the COVID-19 pandemic). However, the falsehood of a teaching is not per se a reason to forbid it. Consequently, it is difficult to envisage a prohibition of the teaching of pseudoscience or of the diffusion of fake news simply because they are false.